Effects of exenatide and liraglutide on heart rate, blood pressure and body weight: systematic review and meta-analysis - Robinson, L; Holt, T; Rees, K; Randeva, H; O'Hare, J (BMJ Publishing Group, 2013)
OBJECTIVES: To synthesise current evidence for the effects of exenatide and liraglutide on heart rate, blood pressure and body weight. DESIGN: Meta-analysis of available data from randomised controlled trials comparing Glucagon-like peptide-1 (GLP-1) analogues with placebo, active antidiabetic drug therapy or lifestyle intervention. PARTICIPANTS: Patients with type 2 diabetes. OUTCOME MEASURES: Weighted mean differences between trial arms for changes in heart rate, blood pressure and body weight, after a minimum of 12-week follow-up. RESULTS: 32 trials were included. Overall, GLP-1 agonists increased the heart rate by 1.86 beats/min (bpm) (95% CI 0.85 to 2.87) versus placebo and 1.90 bpm (1.30 to 2.50) versus active control. This effect was more evident for liraglutide and exenatide long-acting release than for exenatide twice daily. GLP-1 agonists decreased systolic blood pressure by -1.79 mm Hg (-2.94 to -0.64) and -2.39 mm Hg (-3.35 to -1.42) compared to placebo and active control, respectively. Reduction in diastolic blood pressure failed to reach statistical significance (-0.54 mm Hg (-1.15 to 0.07) vs placebo and -0.50 mm Hg (-1.24 to 0.24) vs active control). Body weight decreased by -3.31 kg (-4.05 to -2.57) compared to active control, but by only -1.22 kg (-1.51 to -0.93) compared to placebo. CONCLUSIONS: GLP-1 analogues are associated with a small increase in heart rate and modest reductions in body weight and blood pressure. Mechanisms underlying the rise in heart rate require further investigation.